Ilanon weaving (a case study on Ilanon weaving in Bato, Sta. Cruz, Davao del Sur) - Guden, Jennyvi Ellivera
Ilanon Weaving (A Case Study on Ianon Weaving in Bato Sta. Cruz, Davao del Sur) reflected the renewal of interest in heathen artifacts particularly handwoven textiles. The study gave an overview and description of the different aspects of Ilanon weaving such as the weaving patterns, various fabric colors utilized, weaving methods and techniques adopted, material and machinery used, and the end-products of the woven materials, and their impact on the community and cultural importance. This weaving mirrored the Philippine minorities' ingenuity, adaptability and competence, as it boosted loomweaving activities in small ethnic communities. The adaptation of Ilanon weaving was an attainment and proved to be significant to the community for the provision of livelihood and employment. It conveyed traditional beliefs and values highly regarded. The case study gave a comprehensive and detailed study and analysis of the Ilanon weaving. Basic research on available literature and data pertaining to the study was also undertaken. This was complemented by interviews of key informants and knowledgeable people, site visits to weaving centers and observation tours. Data gathered were collated and organized in appropriate table formats and textual presentation, followed by an interpretation of the data gathered.